An account of some recent discoveries in hieroglyphical literature and Egyptian antiquities : Including the author's original alphabet, as extended by Mr. Champollion, with a translation of five unpublished Greek and Egyptian manuscripts - Young, Thomas, 1773-1829, (Cambridge University Press, 2010)
Thomas Young (1773-1829) was an English physician who was one of the first modern scholars to attempt to decipher ancient Egyptian hieroglyphs. This book, first published in 1823, provides a summary of Young's hieroglyphic research, which he believed Champollion had used without acknowledgement in his important 1822 translations.